Implementation of Collaborative-Humanistic Supervision by the Principal to Strengthen Discipline and Improve Teacher Performance: A School Action Research at MTs Darul Ulum Purwogondo - Abdurokhman Abdurokhman; Susi Erviana; Fetty Hermawati; Soedjono Soedjono (Journal of Educational Sciences, 2026)
Improving teacher professionalism is essential for enhancing the quality of education, particularly in terms of discipline and instructional performance. This study aims to examine the implementation process of collaborative–humanistic supervision conducted by the principal through cyclical School Action Research at MTs Darul Ulum Purwogondo, to analyze changes in teacher discipline across the pre-cycle, Cycle I, and Cycle II, and to evaluate improvements in teachers’ instructional performance resulting from sustained supervision. Employing a School Action Research design across two cycles, data were collected through questionnaires, structured classroom observations, documentation, interviews, and field notes. The findings indicate that teachers’ administrative completeness, punctuality, and instructional process discipline improved significantly, while lesson planning, instructional delivery, and assessment practices became more structured, interactive, and reflective. Qualitative findings reveal reduced teacher anxiety, strengthened trust, increased self-reflection, and enhanced collaborative problem-solving. Supporting factors included empathetic principal communication, structured supervision procedures, and a collaborative school culture, while inhibiting factors such as limited time and initial resistance from senior teachers declined by Cycle II. The study concludes that collaborative–humanistic supervision effectively strengthens teacher discipline.